ANALISIS KESIAPAN GURU PAI DALAM IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DI SMK MUHAMMADIYAH 2 MALANG - Kamila, Cahya Ayu; Taufiq, Hadi Nur; Yusuf, Zulfikar (PAI RAFAH, 2024)
Change is a necessity. Teachers should accelerate the process of adjusting to the changes that occur in education. As currently the independent curriculum implements differentiated learning. SMK Muhammadiyah 2 Malang is one of the first-generation schools in Malang to implement the Merdeka curriculum. Entering two years of this curriculum being offered and implemented at the school, the researcher wants to know the extent of the PAI teacher's readiness to implement differentiated learning in the independent curriculum. For this reason, this study aims to analyze the readiness of PAI teachers to implement differentiated learning in the Merdeka Curriculum at SMK Muhammadiyah 2 Malang. This research uses a qualitative approach with a case study type. For data collection, observation, interviews, and documentation were used. The main data sources in this study are PAI teachers, students, the curriculum vice principal, and the principal of SMK Muhammadiyah 2 Malang. The data analysis technique used the concept of Miles and Huberman. Based on the results of this study, it was found that PAI teachers at SMK Muhammadiyah 2 Malang have implemented four indicators of differentiated learning implementation steps. However, one of the indicators in planning learning needs to be reinforced considering that some students have not been facilitated according to their individual learning needs.